Local Government Policy in Improving Access to Mental Health Services in Tangerang City (Case Study of Karawaci Baru Health Center) - Hidayati, Anisa Hidayati; Widyawati, Tito Inneka; Aditya, Toddy (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2024)
Access to mental health services at puskesmas is often limited, so the role of local government is critical in developing strategies to improve access to mental health services. Puskesmas Karawaci Baru is one of the health centers in Tangerang City that provides mental health services. This study aims to analyze how local government policies improve access to mental health services at Puskesmas Karawaci Baru in Tangerang City, and identify factors that hinder access to mental health services at Puskesmas Karawaci Baru in Tangerang City. The research method used is descriptive qualitative. Qualitative data collection techniques through interviews. The results showed that Puskesmas Karawaci Baru has implemented various strategies, including socialization, providing access to services, infrastructure, and government policies. However, the lack of public knowledge about mental health problems is one of the obstacles in improving mental health services at the health center. For this reason, the government is expected to involve various groups so as to help the community to realize and appreciate the importance of maintaining physical and mental health.